Unusual AIP mutation and phenocopy in the family of a young patient with acromegalic gigantism. (9th February 2018) - Imran, Syed Ali; Aldahmani, Khaled A; Penney, Lynette; Croul, Sidney E; Clarke, David B; Collier, David M; Iacovazzo, Donato; Korbonits, Márta
Summary: Early-onset acromegaly causing gigantism is often associated with aryl-hydrocarbon-interacting receptor protein ( AIP ) mutation, especially if there is a positive family history. A15y male presented with tiredness and visual problems. He was 201 cm tall with a span of 217 cm. He had typical facial features of acromegaly, elevated IGF-1, secondary hypogonadism and a large macroadenoma. His paternal aunt had a history of acromegaly presenting at the age of 35 years. Following transsphenoidal surgery, his IGF-1 normalized and clinical symptoms improved. He was found to have a novel AIP mutation destroying the stop codon c.991T>C; p.*331R. Unexpectedly, his father and paternal aunt were negative for this mutation while his mother and older sister were unaffected carriers, suggesting that his aunt represents a phenocopy. Learning points: Typical presentation for a patient with AIP mutation with excess growth and eunuchoid proportions. Unusual, previously not described AIP variant with loss of the stop codon. Phenocopy may occur in families with a disease-causing germline mutation.